Effects of Recombinant Human Soluble Thrombomodulin (rhs-TM) on Clot-induced Coagulation in Human Plasma - Mohri, Mitsunobu; Suzuki, Makoto; Sugimoto, Emika; Sata, Minako; Yamamoto, Syuji; Maruyama, Ikuro (Thrombosis and Haemostasis, 1998)
Recent studies have suggested that clot-bound thrombin plays an important role in thrombus growth. In this study, we examined the effects of recombinant human soluble thrombomodulin (rhsTM) on clot-induced coagulation. rhsTM enhanced the activation of protein C by clots, and attenuated clot-induced thrombin generation and fibrinopep-tide A (FPA) production in a dose-dependent manner. The inhibitory effect of rhsTM was abolished by anti-protein C antibody. The inhibitory effect of rhsTM on clot-induced thrombin generation continued for over 60 min after the addition of the clot, while an active site-directed thrombin inhibitor, argatroban, produced a more transient inhibition. rhsTM also inhibited the regrowth of the clot in 125I-fibrinogen-supplemented plasma. We also examined the effect of rhsTM by thromboelastography; rhsTM reduced the growth of the clot but had little effect on the time to begin clotting, while heparin and Fragmin (low molecular weight heparin) had effects opposite to those of rhsTM.These findings suggest that rhs-TM attenuates the growth of the clot by activating protein C and inhibiting further thrombin generation in the clot.